Answer:
2Al + 3CuO ⟶ Al₂O₃ + 3Cu
Explanation:
Al + CuO ⟶ Al₂O₃ + Cu
1. Put a 1 in front of the most complicated-looking formula (Al₂O₃):
Al + CuO ⟶ 1Al₂O₃ + Cu
2. Balance Al:
We have fixed 2 Al on the right. We need 2 Al on the left. Put a 2 in front of Al.
2Al + CuO ⟶ 1Al₂O₃ + Cu
3. Balance O:
We have fixed 3 O on the right. We need 3 O on the left. Put a 3 in front of CuO.
2Al + 3CuO ⟶ 1Al₂O₃ + Cu
4. Balance Cu:
We have fixed 3 Cu on the right. We need 3 Cu on the right. Put a 3 in front of Cu.
2Al + 3CuO ⟶ 1Al₂O₃ + 3Cu
Every formula now has a coefficient. The equation should be balanced.
5. Check that atoms balance:
Atom On the left On the right
Al 2 2
Cu 3 3
O 3 3
The balanced equation is
2Al + 3CuO ⟶ Al₂O₃ + 3Cu